(untitled) (Nexo Revista Científica, 2022)
The problem of optimization of construction at all stages of the life cycle of a construction object is one of the most significant. The solution to this problem is the introduction of cyber-physical systems and technologies. The issues of introducing digital tools in construction have been of long-term interest to both researchers and practitioners, since these processes provide construction companies with additional economic benefits, reduce lead times and improve the quality of finished construction products. The article defines the main types of cyber-physical systems and technologies that have the potential for development the economy in the context of digitalization, identifies the main problems of introducing digital tools by small construction enterprises, systematizes and groups indicators for evaluating the effectiveness of their implementation. The authors propose three groups of performance indicators, including performance indicators of construction processes at the stages of the life cycle, performance indicators for the implementation of a construction process management system based on information systems and technologies, performance evaluation indicators for the implementation of investment projects for the implementation of cyber-physical systems and technologies in construction. The results of the study can be used to develop recommendations for improving the efficiency of construction processes based on the introduction of cyber-physical systems and technologies.